The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages Health in Industry and Nutrition. Set out below are the proposals for the improvement of health in industry and the general nutrition of the people. These were endorsed unanimously by the Conference. (a) Health in Industry. The Government has taken some important steps during the war to improve health in the factories and pits. An Industrial Health Committee and a Mines Medical Service have been set up and the Inspector of Factories has used war-time powers to require factories engaged on Governmental orders to set up medical, nursing, and welfare services. Health conditions generally, however, still leave much to be desired. Among the serious shortcomings are :— 1. Factory, Medical and Welfare staffs are paid by and removable by managements. They lack independence to enforce the healthiest conditions. For example : a Medical Officer at a large Tyneside factory has publicly stated that periodical rest-breaks are beneficial to women's health and to production. Yet the management refuse to arrange for such breaks when approached by the shop stewards and state that the opinion of the Medical Officer is just his own and does not necessarily express the views of the management. In some cases workers complain that the factory doctor and Welfare Officers are more concerned with keeping men and women at work than about keeping them healthy. Particularly strong is the criticism of the miners of the attitude of "Compensation doctors." 2. Factory, Shipyard and Mines medical services in the North-East are in the main, of the most primitive kind. Only one firm has a full-time doctor and he is responsible for tens of thousands of workers. Factory doctors, as a rule, are fully occupied with individual patients and have little or no time for their real job, namely, to concern themselves with the effect on health of the industrial processes and the conditions of work and to plan for general factory health improvement. 3. Shortage of Factory Inspectors. It is estimated that there is one Inspector for every thousand factories and one medically qualified Inspector for 25,000 factories. 4. Medical Officers of Health have no powers to influence conditions, other than sanitation, in places of work. On the railways the position is even worse because the Factory Acts do not apply to them. 5. North-East factories and shipyards being nearly all of considerable age, are in many repects [respects] well below the general level of sanitary and health conditions prevailing throughout the country. Particularly serious is the effect on health of the pollution of the Tyne. The untreated sewerage of many places is discharged into the river along whose banks lies the greatest part of Tyneside's engineering and shipbuilding industry. 6. Long working hours, often excessive travelling and general lack of facilities for recreation. 19 15X/2/103/295